2009
DOI: 10.1177/0146167209350326
|View full text |Cite
|
Sign up to set email alerts
|

Giving Birth to Empathy: The Effects of Similar Experience on Empathic Accuracy, Empathic Concern, and Perceived Empathy

Abstract: This study examined how having had a similar experience to a target person's experience affected three facets of empathy: empathic concern, empathic accuracy, and perceived empathy. Women who had never been mothers, who were pregnant with their first child, or who had just given birth to their first child (20 in each group) served as perceivers, watching videotapes of new-mother targets (N = 20) and providing measures of emotional and cognitive empathy. When perceivers had experienced the same life events as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
126
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 36 publications
9
126
0
2
Order By: Relevance
“…In addition to the same dependent measures as in experiment 2, participants also indicated the similarity of past events with the currently presented scenarios of need. This measure was included because having personally experienced similar episodes in one's past has been shown to increase empathy for others, and therefore the degree of relatedness may modulate prosocial intentions in the current study (28,29) (further details are in Materials and Methods and Supporting Information).…”
Section: Significancementioning
confidence: 99%
“…In addition to the same dependent measures as in experiment 2, participants also indicated the similarity of past events with the currently presented scenarios of need. This measure was included because having personally experienced similar episodes in one's past has been shown to increase empathy for others, and therefore the degree of relatedness may modulate prosocial intentions in the current study (28,29) (further details are in Materials and Methods and Supporting Information).…”
Section: Significancementioning
confidence: 99%
“…Although the use of short vignettes may have meant that participants in this study did not engage to the same extent as those of previous studies using extended vignettes (e.g., Batson et al, 1996;Hodges et al, 2010), an examination of mean scores on the empathic concern and personal distress measures indicated that participants reported moderate to high emotional engagement with the scenarios. In many of the studies that have found an effect of similar past experience on empathic outcomes, the researcher either classified the participant as having had a similar experience (Barnett et al, 1987;Batson et al, 1996) or chose participants on the basis of an objective similar experience such as motherhood (Hodges et al, 2010). For participants in the present study, who determined their own similarity, there may be more proximally-related variables to consider such as the degree of connection made.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, a number of studies provide general support for a link between previous similar experience and emotional empathic reactions (e.g., Barnett, 1984;Barnett, Tetreault, Esper, & Bristow, 1986;Barnett, Tetreault, & Masbad, 1987;Hodges, Kiel, Kramer, Veach, & Villanueva, 2010;Stotland & Dunn, 1963). Here, there seems to be a pronounced gender difference, with females displaying greater empathic reaction (e.g.…”
Section: Paused Hoping He'd Make a Tiny Connection Between His Ownmentioning
confidence: 89%
See 1 more Smart Citation
“…As with other empathy theories, the observer must notice the target's emotion expression or situation. If the observer is situations, then this might be one reason why people are more sympathetic toward each other when they have had similar experiences (Barnett, Tetreault, & Masbad, 1987;Hodges, Kiel, Kramer, Veach, & Villanueva, 2010)-those who lack experience are not sure how to make an appraisal.…”
Section: Appraisal and The Non-matching Unemotional Observermentioning
confidence: 99%